Архетип Ославленої Мадонни у літературно-музичному дискурсі: кордоцентризм української не-долі - Драганчук, Вікторія Миколаївна; Drahanchuk, Viktoriia M. (Інститут проблем сучасного мистецтва НАМ України, 2015)
У статті досліджується втілення жіночих образів Маленької Мар’яни, Лілеї, Відьми, Наймички, Катерини як варіантів архетипу Ославленої Мадонни у музичному дискурсі за поезією Т. Шевченка. Аналізуються твори М. Лисенка, М. Аркаса, М. Вериківського, В. Кирейка, Л. Дичко, В. Сильвестрова та ін. У контексті розуміння поняття архетипу К. Г. Юнґом пропонуються поняття «інваріантний архетип» і «варіантний символ-архетип». Символ-архетип Катерини пов’язується з особистою не-долею Т. Шевченка та кордоцентричною не-долею України. А шлях від «покривдженості» України до Божественної висоти, показаний у мета-музиці В. Сильвестрова, трактується як варіант виправлення архетипу. / The purpose of this article is analyze one of the major archetypes Women as a Defamed Madonna in Ukrainian musical discourse, and the main task is a review of said archetype in the T. Shevchenko’s works and its musical interpretations. The embodiment of female characters of Little Mariana, Lily, Witch, Wench and Defamed Madonna Catheryna in the music by the poetry of T. Shevchenko is studied in this article. The works by M. Lysenko, M. Arkas, M. Verykivsky, V. Kyreyko, L. Dychko, V. Sylvestrov and other are analyzes. The term “invariantly archetype” and “variantly symbol-archetype” are offered. Catheryna symbol-archetype is associated with T. Shevchenko own non-fortune and cardiocentry Ukraine non-fortune.

The national thinking and myths creation functioning based on archetypes, which are essentially marks concluded during millennia code system and implement community mental program. During long-term operation in the information environment (from mythology and folklore to authors culture artefacts) with stable semantic load a particular archetype becomes as powerful mental prototype-symbol. Expressing particular universal idea, the archetypes programmed the mentality carriers to thought thinking and behaviours patterns. That is, in these “primary models” concluded the collective representation of certain role models – Mother and Great Mother, Father and Wise Old, Hero, Girls and others. The modern science in understanding the archetypes tend appeals to analytical psychology of C. G. Jung, who treats archetypes as structure-forming elements of the collective unconscious, independent semantic models of unconscious mental activity and spontaneous activity that form the mental and behavioural programs.
Defamed Madonna archetype in a musical discourse: the cardiocentrism of Ukrainian non-fortune
Keywords: інваріантний архетип; варіантний символ-архетип; архетип Ославленої Мадонни; Жінка-Україна; музичне втілення; invariantly archetype; variantly symbol-archetype; Defamed Madonna archetype; archetypal Woman-Ukraine; musical embodiment